Willingness to Communicate in Instructed Second Language Acquisition Combining a Macro- and Micro-Perspective - Mystkowska-Wiertelak, Anna; Pawlak, Mirosław (Second Language Acquisition, 2017)
This book offers a comprehensive account of individual differences variables as well as contextual factors that impinge on second language learners’ willingness to communicate (WTC). Firstly, it adopts a macro-perspective on WTC, which entails an attempt to identify variables that are related to WTC, taking into account the specificity of the Polish higher education setting. Secondly, it embraces a micro-perspective on WTC, striving to pinpoint the individual and contextual influences on levels of WTC in the course of regularly-scheduled, naturally-occurring English classes, as well as to capture the dynamic nature of WTC during such classes. Together, these perspectives bring the reader closer to understanding the mechanisms underlying WTC in specific contexts, thereby providing a basis for recommendations for classroom practice that could translate into learners’ success. It will be of interest to second language acquisition researchers and students, as well as to methodologists and materials writers who can use the research findings to improve the practice of teaching and learning speaking in the language classroom